Analisis Manajemen Transportasi Pada Angkutan Mini Bus - Rahmi Sarafina; Bukhari Usman; Yulfitra Adamy (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This study aims to analyze the management of mini bus transportation at PT. Mulia Wisata Perkasa Banda Aceh which is seen in terms of strengths, weaknesses, opportunities and obstacles. The research is descriptive and uses primary data as a source of data obtained through interviews with respondents. Data analysis using SWOT methods and cartesius diagrams. The results of the study show that the right strategy is applied to PT. Mulia Wisata Perkasa is currently implementing the SO (strength and Opportunities) strategy, with strength 2 and opportunites 1.63. Based on the Cartesian diagram, PT. Mulia Wisata Perkasa has been on the right track by continuing to strategy growth. SO strategies (strength and opportunities) are carried out to utilize the company's strengths to capture the opportunities that the company has. The strategy pursued through efforts to provide promotion to the desired consumer market, providing quality assurance for the products (services) offered, and providing maximum service to consumers.